PENERAPAN PEMASARAN DIGITAL DALAM PENGEMBANGAN PAKET WISATA DESA BLIMBINGSARI, JEMBRANA, BALI - Ni Putu Dyah Krismawintari; I Gusti Bagus Rai Utama; Gerson Feoh (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The PKM Implementation Team has carried out training to solve partner problems in 3 fields: Field 1: Management and Marketing, Field 2: Tourism, and Field 3: Informatics. This activity has been carried out: (1) POKDARWIS has been able to make a tourist map in the form of narration and educational packages that have been integrated and which areas and products are suitable for inclusion in tourism potential. The products used are printing products made from organic colors, forest honey products, and pastry products made from local ingredients. (2) Villagers have collectively agreed on prices and products that can be linked between one tour and another. Currently, the agreement is on the distribution of group guests who spend the night in Blimbingsari Tourism Village. (3) POKDARWIS has been able to rebrand according to current tourism needs such as the entrance to the tourist village, the availability of exciting photo spots, and the creation of tour packages for Blimbingsari village. The rebranding that has been built is that Blimbingsari Tourism Village is The Promised Land. From the feedback that has been given, there are 2 indicators that are the weak points of Blimbingsari Tourism Village, namely the distance of the tourist village from the Denpasar City Center which must take quite a long time around 3 hours because the space is quite far, which is around 120 km. This problem has been overcome by creating a tour package to stay in the village and stringing it through a route that passes through the tourist attractions along the Denpasar-Gilimanuk route, or Denpasar-Singaraja-Gilimanuk. This tour package is designed to add value to the trip and add a more exciting tourist experience